Ukrainian theatre studies in the first three decades of the 20th century. Working with sources materials = Ukraińskie studia teatralne w pierwszych trzech dekadach XX wieku. Praca z materiałami źródłowymi - Korzhova, Anastasiia (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article attempts to identify leading Ukrainian theatre historians of the first third of the 20th century methodological principles based on the analysis of their texts. It was established that the approach of theatre experts from this period to the study of source materials resulted from the academic tradition of historical and philological disciplines, from which theatre studies emerged, and from the process of self-identification of theatre science.
Keywords: Franko, Iwan (1856-1916); Peretz, Wladimir (1870-1935); Rezanow, Wladimir (1867-1936); teatr; metodologia badawcza źródeł historycznych; Franko, Ivan (1856-1916); Peretz, Volodymyr (1870-1935); Rezanov, Volodymyr (1867-1936); theatre study methodology; historical sources research